Uptake and distribution of carbofuran and its metabolites in watermelon (Citrullus lanatus) - Christine Jinang; Patricia Rachel Roney; Margaret Abat (Penerbit Universiti Kebangsaan Malaysia, 2023)
Carbofuran is toxic to humans and the environment, and its misuse in agriculture results in the violation of Maximum Residue Limits (MRL) for most crops. The use of carbofuran in Malaysia is to be banned effectively in May 2023. Limited data were published on the uptake and distribution of carbofuran and its metabolites for most crops. Therefore, a study was conducted to assess carbofuran residues in watermelon grown at the Agriculture Research Centre, Semongok. Carbofuran at 17 kg/ha and 34 kg/ha were applied to watermelon planted under the recommended agronomic practices. The plants were sampled at periodic intervals over 63 days after being treated with carbofuran. The carbofuran and their metabolites in the watermelon leaf, stem, and fruits were determined using a liquid chromatography equipped with a triple quadrupole mass spectrometer. The carbofuran residues were observed up to 35 days after application and reached below the quantification level (0.01 mg/kg) at 42 days after application. Residues were concentrated in the roots and stems for both treatments. About 80 to 90% of the carbofuran was metabolized to carbofuran-3-hydroxy in the watermelon leaves, and 50% in the stems. The highest residue level of carbofuran for application at 17 kg/ha was recorded on Day 9 for roots (0.192 mg/kg), Day 21 for leaves (0.057 mg/kg), and Day 5 for stems (0.134 mg/kg). At 34 kg/ha, the highest carbofuran residues concentrations were recorded on Day 5 for root (0.446 mg/kg) and stem (0.151 mg/kg), and Day 3 for leaves at 0.303 mg/kg. Traces of carbofuran residues were detected in the skin and flesh of the fruit. The carbofuran residue levels in watermelon fruit were below the established MRL of 0.01 mg/kg. Our findings suggest that a proper postharvest interval shall be observed.